Informações de hóspedes sobre a comunicação ambiental em meios de hospedagem - Bringmann, Deise Renata (My University, 2019)
Environmental communication is a management tool in the means of hosting. In order to analyze how the environmental communication is internalized in these tourist enterprises, an exploratory / descriptive research was carried out. For this, the questionnaire was used as data collection technique. It presents closed questions (single and multiple choice) and open questions related to the existence of environmental communication and sustainable practices implemented in the means of lodging and criteria for the selection of these projects by the guests. The questionnaires were applied to people who are staying in lodging facilities, guests of three lodging facilities, participants of an academic event, and to a group of Professors Researchers of the Stricto Sensu Postgraduate Programs of the University of Caxias do Sul. The lodging facilities are located in the municipality of Canela and Caxias do Sul. Among the selected lodging facilities, two develop actions aimed at the management of environmental sustainability. The results allow to conclude that the communication is scarce in the means of lodging (24.24% of the indications). The most used means of communication according to respondents were: display or plaque (17.71%); Informative (12,15%) and Folder or manual (11,46%). Among the sustainable practices disclosed are: reduction of water consumption (17.92%); consumption of water (12.74%), energy consumption (10.85%) and reduction of energy consumption (10.61%). It was also possible to identify that, in general, the sustainable practices divulged / implemented in the means of lodging are not decisive factors for the choice of means of lodging (37,58% never thought about the subject). It is concluded that efforts for sustainability must overcome the barrier of insignificance, internalizing in the management of the means of the lodging the sustainable actions and socializing them internally and externally. In this sense, the implementation of environmental communication and its constant evaluation, allow establishing important relations between the tourist service and the user, contributing to the continuous improvement of the means of accommodation.
A comunicação ambiental é um instrumento de gestão nos meios de hospedagem. No sentido de analisar como a comunicação ambiental é internalizada nesses empreendimentos turísticos, foi realizada uma pesquisa de caráter exploratório/descritiva. Para tal, foi utilizada como técnica de coleta de dados o questionário. O mesmo apresenta perguntas fechadas (de única e de múltipla escolha) e abertas relacionadas à existência da comunicação ambiental e de práticas sustentáveis implantadas nos meios de hospedagem e critérios de seleção desses empreendimentos pelos hóspedes. Os questionários foram aplicados para pessoas que se hospedam comumentemente em meios de hospedagem, (hóspedes de três meios de hospedagem) participantes de um evento acadêmico, e para um grupo de professores Pesquisadores dos Programas de Pós-Graduação Stricto Sensu da Universidade de Caxias do Sul. Os meios de hospedagem estão localizados no município de Canela e de Caxias do Sul. Dentre os meios de hospedagem selecionados, dois desenvolvem ações voltadas à gestão da sustentabilidade ambiental. Os resultados permitem concluir que a comunicação é escassa nos meios de hospedagem (24,24% das indicações). Os meios de comunicação mais utilizados de acordo com os respondentes foram: display ou placa (17,71%); Informativo (12,15%) e Folder ou manual (11,46%). Dentre as práticas sustentáveis divulgadas destacam-se: redução do consumo de água (17,92%); consumo de água (12,74%), consumo de energia (10,85%) e redução do consumo de energia (10,61%). Também foi possível identificar que, em geral, as práticas sustentáveis divulgadas/implantadas nos meios de hospedagem não são fatores decisivos para a escolha dos meios de hospedagem (37,58% nunca pensaram no assunto). Conclui-se que os esforços em busca da sustentabilidade devem ultrapassar a barreira da insignificância, internalizando na gestão dos meios de hospedagem as ações sustentáveis e socializando-as internamente e externamente. Nesse sentido a implantação da comunicação ambiental e sua constante avaliação, permitem estabelecer importantes relações entre o serviço turístico e o usuário, contribuindo com a melhoria contínua dos meios de hospedagem.
Keywords: Indústria hoteleira - Aspectos ambientais; Sustentabilidade; Comunicação; Hotel industry - Environmental aspects; Sustainability; Communication